The Impact of Previous Cesarean Delivery on Preterm Birth: A Comprehensive Review - Albagir Mahdi Ahmed Hassan (International Journal of Medical Toxicology and Legal Medicine, 2024)
Obstetric complication in preterm birth has significantly affected both mothers and their new-borns; therefore, increasing the incidence for women with previous history of cesarean delivery. It leads to complications, like uterine rupture, cervical insufficiency, and abnormality of the placenta, with a likelihood that increases chances for preterm births. Such pregnancies may also be further sub-classified under spontaneous or medically indicated categories. Spontaneous preterm birth is largely attributed to complications like uterine rupture, that is, with more severe outcomes; however, medically indicated premature birth, mostly due to the mother’s health issues or fetal distress, has risks for neonatal respiratory complications. The more cesarean deliveries, the higher is the risk of preterm birth. With multiple repeat cesarean deliveries, the risk of complications like placenta previa and placenta accreta due to cumulative uterine scarring and adhesions increases as well. Short interpregnancy intervals may pose particular risks for preterm birth, especially for intervals under 18 months; complications such as uterine rupture and abnormal placentas contribute to these risks. Obesity and advanced maternal age are maternal variables that enhance the risk of preterm birth following cesarean delivery. Preeclampsia, diabetes, and gestational hypertension are added risks associated with obesity. In order to enhance outcomes for moms and newborns, the report emphasizes early intervention, meticulous risk factor control, and proper birth spacing. To enhance the health of the mother and the baby and reduce the likelihood of preterm delivery in women who have had prior cesarean sections, a better understanding of the complex relationships between these factors is necessary.